1925 Nev. Stat. 54, § 2 - (:unkn) unknown (My University, 1925)
Ch. 47, § 2: Prohibited noncitizens and convicts from owning, possessing, or having under their custody or control any pistol, revolver, or concealable firearms; violators subject to felony conviction and imprisonment of 1-5 yrs.
Keywords: POSSESSION - DANGEROUS PERSONS